The Effect of Calcium on Biomarkers of Ovarian Fertility in Premature Ovarian Failure: A Systematic Review - Sutrisno Sutrisno; Tri Aji Bangun Nuswantoro (Asian Journal of Health Research, 2023)
Introduction: Premature ovarian failure (POF) is a condition in which ovarian function decreases or follicles are depleted in women aged less than 40 years. Calcium, along with vitamin D, is a mineral with many benefits for the reproduction system. This review is written to observe the effect of calcium on ovarian fertility biomarkers in premature ovarian failure. Methods: The literatures search was conducted utilizing numerous search engines, namely PubMed, Cochrane, Springer, Science Direct, Nature, and Google Scholar. Article publication year was restricted from 2016 to 2022. Article search keywords included â€œcalciumâ€, â€œvitamin Dâ€, â€œpremature ovarian failureâ€, â€œpremature ovarian insufficiencyâ€, â€œamenorrhoeaâ€, â€œovarian reserve biomarkersâ€, â€œestradiolâ€, â€œfollicle stimulating hormoneâ€, and â€œluteinizing hormoneâ€. Article selection was performed using the preferred reporting items for systematic review and meta-analysis protocols guidelines (PRISMA-P). The first authorâ€™s name, publication year, samples number, age range of subjects, duration of data collection, geographical setting, study design, and conclusions of research results were extracted from the selected paper. Results: 8397 articles were obtained from the six search engines. 13 articles met the inclusion criteria. Research conducted by Iran reported a significant correlation between vitamin D levels and AMH levels (p<0.001). In comparison, the research in Bangladesh showed a significant positive correlation between vitamin D levels and AMH levels (r=0.433; p=0.001) and vitamin D levels and AFC values (r=0.419; r=0.001). However, 11 other researchers reported contradictory results. Conclusion: The calcium and vitamin D effect on reproductive health related to POF occurrence is still inconsistent. Therefore, observational and experimental research is needed to analyze this topic.